Refugee boy - Zephaniah, Benjamin (New York : Distributed by St. Martin's Press, 2001)
Fourteen-year-old Alem Kelo adjusts to life as a foster child seeking asylum in London, while his Eritrean mother and Ethiopian father work for peace between their homelands in Africa.
Booklist.
Books for the Teen Age (NYPL).
Publisher's Weekly.
Young Adult
Keywords: Eritrean-Ethiopian War, 1998- -- Juvenile fiction; Asylum, Right of -- England -- Fiction; Eritrean-Ethiopian War, 1998- -- Fiction; Foster home care -- Fiction; Refugees -- England -- Fiction; Asylum -- Fiction; Eritrean-Ethiopian War, 1998- -- Fiction; Foster home care -- Fiction; Refugees -- England -- Fiction; London (England) -- Fiction; London (England) -- Fiction